2016
DOI: 10.1634/theoncologist.2015-0327
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Economic Impacts of Skeletal-Related Events Among Medicare Enrollees With Prostate Cancer Metastatic to Bone

Abstract: Background. Approximately 40% of men diagnosed with metastatic prostate cancer experience one or more skeletalrelated events (SREs), defined as a pathological fracture, spinal cord compression, or surgery or radiotherapy to the bone. Accurate assessment of their effect on survival, health care resource utilization (HCRU), and cost may elucidate the value of interventions to prevent SREs. Materials and Methods. Men older than age 65 years with prostate cancer and bone metastasis diagnosed between 2004 and 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…A more recent study using almost 3,297 men from SEER-medicare found that among men with metastatic prostate cancer, those with >1 SRE had greater than twofold risk of death versus those with no SREs. 13 Although the reference group was men with bone metastases but no SREs, the study did not restrict to those with CRPC. Finally, another study used nearly 7,000 men diagnosed with metastatic PC between 2000–2007 from SEER-Medicare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study using almost 3,297 men from SEER-medicare found that among men with metastatic prostate cancer, those with >1 SRE had greater than twofold risk of death versus those with no SREs. 13 Although the reference group was men with bone metastases but no SREs, the study did not restrict to those with CRPC. Finally, another study used nearly 7,000 men diagnosed with metastatic PC between 2000–2007 from SEER-Medicare.…”
Section: Discussionmentioning
confidence: 99%
“…79 Meanwhile, a number of population-based studies found an association between SREs and worse OS. 1013 Although these population-based studies benefited from large sample sizes, they could only capture information on metastases, SREs and disease characteristics from ICD-9 codes. Specifically, these prior observational studies were unable to adjust for bone pain, number of bone metastases, and PSA doubling time (PSADT).…”
Section: Introductionmentioning
confidence: 99%
“…And while there is clear evidence that skeletal related events do confer a poor prognosis,22 there is not comparable evidence for each of the other events included in the composite.…”
Section: Weighing the Benefits And Harmsmentioning
confidence: 97%
“…Risk factors for the subsequent development of bone metastasis include higher Gleason score, higher serum prostate specific antigen (PSA), and shorter PSA doubling time (Moriera et al, 2016). Roughly 40% of men with metastatic prostate cancer develop skeletal related events (SREs) such as a pathologic fracture, spinal cord compression, and the need for surgery or radiotherapy to the involved bone (McDougall et al, 2016). These SREs carry with them substantial economic costs (Perrault et al, 2015), patient discomfort, and reduced cancer specific survival (Koo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%